If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(q + 3) = 4q + q + -9 Reorder the terms: 2(3 + q) = 4q + q + -9 (3 * 2 + q * 2) = 4q + q + -9 (6 + 2q) = 4q + q + -9 Reorder the terms: 6 + 2q = -9 + 4q + q Combine like terms: 4q + q = 5q 6 + 2q = -9 + 5q Solving 6 + 2q = -9 + 5q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-5q' to each side of the equation. 6 + 2q + -5q = -9 + 5q + -5q Combine like terms: 2q + -5q = -3q 6 + -3q = -9 + 5q + -5q Combine like terms: 5q + -5q = 0 6 + -3q = -9 + 0 6 + -3q = -9 Add '-6' to each side of the equation. 6 + -6 + -3q = -9 + -6 Combine like terms: 6 + -6 = 0 0 + -3q = -9 + -6 -3q = -9 + -6 Combine like terms: -9 + -6 = -15 -3q = -15 Divide each side by '-3'. q = 5 Simplifying q = 5
| 5y= | | 12(y-1)-4y=3(y-2)+9y | | 7x-19=6x+53 | | -6x+2=-46 | | 6y-4x=4 | | 5+2x+x=3x-x+8 | | 15x^2-7x-4=0 | | 6-4n=-20 | | 7+2x(3)=4x+9 | | 2f+3=9a-10 | | (6x)7x= | | 4(t-6)+6t=5(2t+4)-8 | | 8+4n=-12 | | Y^2=6Y | | 5*19= | | 5x-19= | | 15+2n=9 | | 7-2(-5x-9)+2x=4(2x-1)+3(x+12) | | -6=24 | | 4-5n=11 | | 24x+27=-36x-6 | | 3y=-72 | | -0.5b+0.44444444444=0.57142857142 | | -6+2x=-4 | | 2y^2-6y+4=0 | | -(6y+2)-(5y-4)=1 | | 4x+13=-78-9x | | 18=7.5h | | 1x-7= | | a^2+3a=2 | | 1.2y=6.84 | | 8-x+5x-3-8x= |